Proteogenomics: New Emerging Technology - Wasim Sajjad; Muhammad Rafiq; Barkat Ali; Muhammad Hayat; Sahib Zada; Wasim Sajjad; Tanweer Kumar (HAYATI Journal of Biosciences, 2016)
The term proteogenomics is basically the integration of proteomics with genomics and transcriptomics. Today, proteogenomics is developing on the way to combined understanding about overall cellular functions. At present globally, structure of genes, expression of genes (in the form of mRNA synthesis), synthesis of proteins (translation of mRNA) and post-translational modification (structural modification of proteins) have turn out to be technically practicable and act as a novel viewpoint to molecular procedures. Current research has proved the importance of proteogenomics technology in cancer for studying molecular signature of tumors particularly in human beings, and its treatment and prevention. Proteogenomics is not restricted to oncology but it also plays a vital role in other areas of life sciences and biomedicines and anticipation can make up these areas. Here in this minireview, we will discuss the latest progress made in recent years, challenges and viewpoints about proteogenomics technology.